Additional Low‐Voltage‐Area Ablation in Patients With Paroxysmal Atrial Fibrillation: Results of the Randomized Controlled VOLCANO Trial. Issue 13 (7th July 2020) - Masuda, Masaharu; Asai, Mitsutoshi; Iida, Osamu; Okamoto, Shin; Ishihara, Takayuki; Nanto, Kiyonori; Kanda, Takashi; Tsujimura, Takuya; Matsuda, Yasuhiro; Okuno, Shota; Hata, Yosuke; Mano, Toshiaki
Abstract : Background: The efficacy of low‐voltage‐area (LVA) ablation has not been well determined. This study aimed to investigate the efficacy of LVA ablation in addition to pulmonary vein isolation on rhythm outcomes in patients with paroxysmal atrial fibrillation (AF). Methods and Results: VOLCANO (Catheter Ablation Targeting Low‐Voltage Areas After Pulmonary Vein Isolation in Paroxysmal Atrial Fibrillation Patients) trial included paroxysmal AF patients undergoing initial AF ablation. Of 398 patients in whom a left atrial voltage map was obtained after pulmonary vein isolation, 336 (85%) had no LVA (group A). The remaining 62 (15%) patients with LVAs were randomly allocated to undergo LVA ablation (group B, n=30) or not (group C, n=32) in a 1:1 fashion. Primary end point was 1‐year AF‐recurrence‐free survival rate. No adverse events related to LVA ablation occurred. Procedural (124±40 versus 95±33 minutes, P =0.003) and fluoroscopic times (29±11 versus 24±8 minutes, P =0.034) were longer in group B than group C. Patients with LVAs demonstrated lower AF‐recurrence‐free survival rates (88%) than those without LVA (B, 57%, P <0.0001; C, 53%, P <0.0001). However, LVA ablation in addition to pulmonary vein isolation did not impact AF‐recurrence‐free survival rate (group B versus C, P =0.67). Conclusions: The presence of LVA was a strong predictor of AF recurrence after pulmonary vein isolation in patients with paroxysmal AF. However, LVA ablation had no beneficial impact on 1‐year rhythm outcomes. Registration: URL: https://www.umin.ac.jp/ctr ; Unique identifier: UMIN000023403.